Estudio del impacto de la modificación de la flota de transporte en la cadena de suministro de un PSL tipo I ubicado en Bogotá. (2022)
The purpose of this project is to analyze all the factors that affect a PSL1 transport company when carrying out a process of renewing its fleet, either gradually or completely. It begins with a preliminary analysis of the company's land logistics operations, this is done in order to evaluate all aspects related to this activity and that may be benefited or affected at the time of carrying out the renewal or maintenance process. its main asset which are the vehicles. All the qualitative and quantitative variables of the transportation system used by the logistics service provider company are identified, such as income, expenses, distribution costs, maintenance costs, administrative expenses and among others that intervene in the operation. An analysis and comparison of the two technologies that are used in the current fleet (EURO III) and the new fleets that are already updated with the technology (EURO V) for the reduction of gases harmful to the environment is also carried out. and the health of the inhabitants, in this way it is intended to clarify if the change of fleet results in having a significant impact on the health and air quality of the city.